The Role of Integrity as a Mediator in Strategic Leadership: A Recipe for Reputational Capital - Worden, Skip (Journal of business ethics, 2003)
In the context of a crisis of confidence in executive leadership in corporate America, this paper examines the role of integrity as a mediator within strategic leadership and its impact on credibility in reputational capital. A tension can occur within strategic leadership between the elements of strategic planning and leadership vision. This tension can destroy the credibility of reputational capital unless strategic leadership is managed effectively. Integrity can be used as the glue providing for credible leadership vision amid a strategic perspective oriented to competitive pressures, thereby enabling strategic leadership to contribute to a sustainable competitive advantage. A strategic leadership audit is presented as a tool by which strategic leadership and reputational capital can be managed.